Design of a tunable graphene plasmonic-on-white graphene switch at infrared range - Farmani, Ali; Zarifkar, Abbas; Sheikhi, Mohammad H.; Miri, Mehdi (Superlattices and microstructures, 2017)
A tunable Y-branch graphene plasmonic switch operating at the wavelength of 1.55 μm is proposed in which graphene is placed on white graphene. The switch structure is investigated analytically and numerically by the finite difference time domain method. The graphene plasmonic switch considered here supports both transverse magnetic and transverse electric graphene plasmons whose propagation characteristics can be controlled by modulating the external electric field and the temperature of graphene. Our calculations show that by strong coupling between the incident waves and the graphene plasmons of the structure, a high polarization extinction ratio of 45 dB and relatively large bandwidth of 150 nm around the central wavelength of 1.55 μm are achievable. Furthermore, the application of white graphene as the substrate of graphene decreases the propagation loss of the graphene plasmons and the required applied electric field. It is also shown that the propagation mode of the graphene plasmons can be tuned by changing the temperature and the calculated threshold temperature is 650 K. •A tunable, compact, and broadband Y-branch graphene plasmonic switch is presented.•The effects of both the electric biasing and temperature are considered for tuning.•White graphene is introduced to obtain low driving voltage and high switching speed.•High extinction ratio of 45 dB and large bandwidth of 150 nm are achievable.